New law on the protection of human rights for populations affected by dams in Brazil - AZEVEDO, Rosaly; LEITE, Carlos (Utopía y Praxis Latinoamericana, 2025)
This article analyzes whether Law No. 14,755/2023, which establishes the National Policy on the Rights of Populations Affected by Dams (PNAB), represents a paradigm shift in human rights protection in Brazil. Using the deductive method, the study explores the concept of a "paradigm shift" in the legal context, the historical struggles led by the Movement of People Affected by Dams (MAB), and the fundamental principles of PNAB, such as democracy, victim centrality, and integral reparation. It also evaluates the applicability of the law to disasters that occurred before its enactment, such as Mariana and Brumadinho. The hypothesis is that PNAB inaugurates a new legal paradigm by breaking away from patrimonialist approaches and prioritizing those affected as central subjects of rights, strengthening socio-environmental protection in Brazil.